مزايـا قواعــد اللغــة العـربيــة وخـصــائـصها - Puji Rahayu (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Arabic language has special features and specifications through others language in this world. Firstly, there are the largest number of arabic vocabullaries. Secondly, a word / a vocabullary could be some meanings or many different meaning while it put to the different sentences. Thirdly, Arabic is a phonetic languange, which means letters corresond to sounds. While this is true of many languages to a certain extent, Arabic is unique in that there aren’t groupof letters creating completly unguessable sound. This means anyone who knows the arabic letters, the sounds they make and the short vowel marking can “sound out” every word. Many other language, in contrast, has many spellings that do not correspond to individual letter sounds, as in the word rough. For this reason, arabic spelling might be considered easier than that many languages, including Indonesian and English.